TBHQ attenuates ferroptosis against 5-fluorouracil-induced intestinal epithelial cell injury and intestinal mucositis via activation of Nrf2 - Shihua Deng (BMC, 2021)
Abstract Background Intestinal mucositis is a common side effect of chemotherapy and radiotherapy. Very few drugs can efficiently ameliorate it. Tertiary butylhydroquinone (TBHQ) is a widely used food preservative with known immunomodulatory activity. Whether it has an effect on intestinal mucositis remains unknown. In this study, we investigated the role and mechanism of action of TBHQ on 5-fluorouracil-induced (5-FU-induced) human intestinal epithelial cell (HIEC) injury and intestinal mucositis in mice. Methods We established a cell model of HIEC injury and a mouse model of intestinal mucositis via treatment with 5-FU. Cell death, Cell Counting Kit-8, and lactate dehydrogenase (LDH) release were assessed for the HIECs. Diarrhea, body weight, intestinal length, mucosal damage, and the levels of IL-6, TNF-α, IL-1β, glutathione, reactive oxygen species, and malondialdehyde were determined for the mice. Additionally, we performed immunohistochemical analysis, immunofluorescence, western blotting, quantitative real-time PCR, and ELISA to examine the effects of TBHQ. Finally, HIECs were transfected with an Nrf2 gene silencer to verify its role in ferroptosis. All data were analyzed using one-way analysis of variance or paired t-tests. Results TBHQ markedly decreased LDH release and cell death and improved the proliferative ability of 5-FU-treated HIECs. The TBHQ-treated mice showed reduced weight loss, a lower diarrhea score, and longer colons than the 5-FU-treated mice. The in vivo expressions of IL-1β, IL-6, and TNF-α were suppressed by TBHQ treatment. Ferroptosis was shown to be involved in 5-FU-induced intestinal mucositis, and TBHQ markedly hampered its activation. Mechanistically, TBHQ activated Nrf2 effectively and selective Nrf2 knockdown significantly reduced the anti-ferroptotic functions of TBHQ in 5-FU-treated HIECs. Conclusions TBHQ attenuates ferroptosis in 5-FU-induced intestinal mucositis, making it a potential novel protective agent against intestinal mucositis.